Association of gene polymorphism in ERG rs2836411 with anemia and susceptibility to aortic dissection - Ying Wang; Gaoshan Li; Fangzheng Zeng; Kunyan Li; Wenxu Pan; Mingle Zhang; Hao Yang; Jun Jin (BMC Cardiovascular Disorders)
Abstract Background The erythroblast transformation-specific related gene (ERG) is expressed in hematopoietic stem and progenitor cells and endothelial cells. This study aimed to investigate if ERG rs2836411 is a novel genetic locus associated with anemia and aortic dissection (AD). Method A case-control trial was conducted to evaluate the association between ERG rs2836411 polymorphism, anemia, and AD risk. The ERG rs2836411 polymorphism was analyzed using Sanger dideoxy chain termination sequencing on genomic DNA extracted from whole blood. Serum erythropoietin (EPO) and interleukin-6 (IL-6) concentrations were measured by enzyme-linked immunosorbent assay (ELISA). Results 119 preoperative AD patients and 119 healthy controls were enrolled, with age and sex matched. Anemia was found independently associated with AD presence (Odds ratio (OR) 20.82, p < 0.001). Remarkably, T carriers (CT + TT) of ERG rs2836411 were associated with anemia in AD patients (OR 2.81, p = 0.013) but not in controls. After adjusting for conventional risk factors including age, sex, smoking and hypertension status, T carriers (CT + TT) were independently associated with AD presence (OR 2.20, p = 0.015), but were not associated if anemia was further adjusted. While EPO concentration was higher in AD patients and was associated with AD presence (OR 1.09, p = 0.006), no difference in EPO levels was observed between the ERG genotypes of AD patients. Conclusions T carriers (CT + TT) of ERG rs2836411 are independently associated with anemia and AD presence. The association between ERG rs2836411 polymorphism and susceptibility to AD may be mediated by anemia. Further studies are warranted to validate whether this association is causal.